Immunomodulatory Effects of Hydrolyzed Debaryomyces Hansenii in Atlantic Salmon (Salmo Salar L): From the in Vitro Model to a Natural Pathogen Challenge After Seawater Transfer - Imarai-Bahamonde, C (Elsevier B.V., 2024)
Non-Saccharomyces yeast such as Debaryomyces hansenii or its cell wall-components are emerging candidates for novel functional aquafeeds, as they contain several microbe-associated molecular patterns (MAMPs) that can activate and modulate the host s physiological responses, thereby improving fish health and welfare. In this study, we combined in vitro work using SHK-1 cell line and primary cultures of head kidney leukocytes (HKL) from Atlantic salmon (HKL), with an in vivo trial in which two groups of Atlantic salmon were fed 0.1% hydrolyzed D. hansenii (LAN6) in freshwater (7 weeks) and seawater (6 weeks). In vitro results by ELISA showed that after induction with LAN6, SHK-1 cells increased the levels of TNFα and iNOS (at 6 h post-induction), while HKL increased TNFα (6 h post-induction) and IL-10 (24 h post-induction), and reduced TNFα levels at 24 h post-induction. In addition, during an early natural pathogen challenge in the seawater stage (week 5), an increase in specific plasma immunoglobulins against Moritella viscosa, along with an upregulation in pathways associated with humoral immunity and complement activation in the liver was detected in vaccinated fish fed LAN6 (Group A). These data suggest that LAN6 was able to modulate the immune response of Atlantic salmon making it a promising functional feed additive for aquafeeds to achieve a more resilient farmed salmon. © 2023 The Authors